The effectiveness of air-cleaning technologies against COVID-19 transmission in healthcare settings - Okokon, Enembe; Chibuzor, Moriam; Ezema, Chisom; Bernard, Moses; Barde, Veronica; Oyo-Ita, Angela; Meremikwu, Martin; , WHO Colleagues (Frontiers in Environmental Health, 2025)
BackgroundThe healthcare setting is a high-transmission-risk environment for COVID-19. Attending clinicians and patients are at risk of infection if measures are not established to secure the microbial safety of the health facility. Air cleaning technologies may deliver a safer clinical environment by depleting airborne viral concentrations.AimThis systematic review aims to assess the effectiveness of air-cleaning methods in preventing COVID-19 transmission in health facilities and the effectiveness of air cleaning rated by microbial depletion.MethodThis study is a rapid systematic review.ResultsNo study assessed COVID-19 transmission relative to the air cleaning methods. HEPA filtration produced a more rapid and thorough removal of aerosols from health facilities. HEPA filtration showed mixed performance in removing COVID-19 viral RNA from a routine care ward and an intensive care unit (ICU). Meta-analyses could not be conducted due to dissimilarities in included studies.ConclusionThe reviewed papers demonstrate that HEPA filtration hastens the depletion of aerosols from the indoor space in the health facility. Further translation of this finding to prevent COVID-19 transmission should assume the relevance of room occupancy density, virus-free outdoor air supply, recirculated filtered air, virus source strength, number of sources, and the use of facemasks by health workers and visitors to the health facility.